PERCEPTION OF PARENTS OF PREGNANT ADOLESCENTS ON SEX EDUCATION - Villas Boas, Janayna Barros Reina; Gomes, Maria Fernanda Pereira; Reticena, Kesley de Oliveira; Capellini, Verusca Kelly; Fracolli, Lislaine Aparecida (Journal of Health Care, 2017)
Objective: To identify the perception of parents about adolescent pregnancy and the sex education offered in schools and basic health units. Methods: Exploratory descriptive qualitative approach. The study was performed at the homes of relatives of pregnant adolescents assisted by the basic health units of the city of Assis (São Paulo, Brazil). Eight parents of pregnant adolescents aged 12-19 years participated in the study. Data collection occurred from July to August 2016 through a semi-structured questionnaire. Data treatment was based in content analysis technique, in which the interviews were submitted to three processes: sorting, classification, and final analysis. From this process, the following topics emerged: knowledge on use of existing contraceptive methods and agreement to the sex education of the adolescents; influence of education on early sex practice and occurrence of pregnancy; impacts of early pregnancy; and parents' position regarding government's intervention in adolescent sex education. Results: It was possible to observe that the parents do not totally oppose the government actions; nevertheless, they claim the parental responsibility in the decision-making related to their children's lives. Conclusion: Social problems generated by early pregnancies must be addressed by government institutions, not only dedicated to the adolescent public, but also including their parents and family.
Keywords: Pregnancy in adolescence; sex education; family relations